A review on carbon trading: new age enterprise for sustainable development and profitability with special reference to UAE. (2017) - Cherian, Jacob; Jacob, Jolly; Farouk, Sherine
This study is an attempt to analyse carbon emission trading with a special focus on United Arab Emirates. The purpose of the study is to assess how far enterprises are able to sustain carbon-trading mechanism and to analyse the quantum of benefits they derive or the liabilities they encounter. The highlight of this paper is on carbon trading with respect to the Kyoto protocol. Further, it has also been elucidated that greenhouse gas emission leads to climate change. With a view to gain carbon credits, mechanisms to reduce emissions such as; clean development mechanism, joint implementation and emission trade have been presented. In this research, various types of instruments for CO2 trade have been presented which is followed by a detailed literature on carbon trading with respect to UAE. The study concludes that carbon trading in general lacks vision but could be implemented by the government through the creation of policies. As a result, enterprise development would go in tandem with sustainable development.